IL-17, IL-21 and IL-22 polymorphisms in rheumatoid arthritis: A systematic review and meta-analysis. - Maria Inês Agonia Ferreira (2020)
Background: Rheumatoid Arthritis (RA) is an autoimmune systemic disease and in its pathogenesis participate several proinflammatory cytokines, including those produced by Th17 cells. We performed a systematic review aiming to assess the associations between polymorphisms in Th17 cytokines, namely IL-17A, IL-17F, IL-21 and IL-22, and susceptibility to RA. Methods: We searched three electronic databases (MEDLINE, Scopus and Web of Science) for observational studies assessing the association between susceptibility to RA (or its clinical presentation) and polymorphisms of the cytokines IL-17A, IL-17F, IL-21 and IL-22. From the selected studies, we extracted information on the studied polymorphisms, assessed outcomes, and demographic characteristics of participants. We performed random effects meta-analyses assessing the associations between susceptibility to RA and different genotypes of the IL- 17A rs2275913, IL-17F rs763780 and IL-17F rs2397084 polymorphisms. Primary studies' quality was assessed using the Q-Genie tool. Results: Fifteen studies were included in this systematic review. Five IL-17A polymorphisms were reported to be associated with susceptibility to RA. For the IL-17A rs2275913 polymorphism, our meta-analysis showed the AA genotype to be significantly associated with lower susceptibility to RA (OR=0.76; 95%CI=0.61-0.93; p=0.01), while the opposite was observed for the GG genotype (OR=1.20; 95%CI=1.06-1.35; p=0.01). Concerning IL-17F rs763780 polymorphism, the TT genotype was found to be significantly less frequent in RA patients (OR=0.49; 95%CI=0.31-0.77; p=0.002), while the opposite was observed for the CT genotype (OR=2.00; 95%CI=1.03-3.87; p=0.04). No significant associations were found regarding rs2397084 polymorphisms. For IL-21, rs6822844 and rs4505848 were described to have significant associations with susceptibility to RA. No studies were found assessing IL-22 polymorphisms in RA. Conclusions: IL-17A rs2275913 and IL-17F rs763780 polymorphisms are significantly associated with susceptibility to RA and with different clinical characteristics of this disease.